Colonialism and Contested Cultures of Victory in the French Empire of the 1920s. (October 2019) - Hassett, Dónal
More than any other belligerent power, France relied heavily on the contribution of her colonies during the First World War. Thus, the triumph over the Central Powers and the culture(s) of victory which emerged from it were undeniably 'imperial'. But what did this mean for the postwar Empire? This article explores the extent to which victory was a disruptive force in France's Empire. It examines how actors of all ideological, social and ethnic backgrounds from across France's colonies articulated their own visions of how victory in the First World War should shape the future of the Empire. It considers their attempts to place the war into their broader narratives of the Empire, past, present and future and thus impose their own ideas of what a just postwar imperial order should look like. Drawing on examples from across the Empire, it underlines the extent to which victory in the First World War gave rise to competing and often opposing demands for a new settlement among colonial administrators, colonial citizens and colonial subjects. In doing so, it teases out the contradictory role played by imperial cultures of victory in simultaneously facilitating contestation of the colonial system and limiting the radicalism of such challenges to Empire.